PENGARUH KOMUNIKASI PIMPINAN TERHADAP KINERJA PEGAWAI DI BIRO ADMINISTRASI PIMPINAN SEKRETARIAT DAERAH PROVINSI RIAU - Yunaz, Fahmi (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
Leadership Communication is one of the factors that influence employee performance. Leaders who have good communication will produce good employee performance as well. The purpose of this study was to determine the effect of leadership communication on employee performance at the Administrative Bureau of the Regional Secretariat of Riau Province. This study uses quantitative methods, with data collection techniques through questionnaires/questionnaires, then analyzed using simple linear regression using the SPSS 26 application. The technique for determining the number of samples used by the authors in this study is purposive sampling in which the determination of the sample is based on the characteristics or features - Certain characteristics based on characteristics or characteristics, namely 30 employees are used as research samples. From the results of the study it can be concluded that the leadership communication variable as a whole influences 15.6% of the employee performance variable. While the remaining 84.4% is influenced by other variables that are not examined in this study.